2007
DOI: 10.1179/174328407x161240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of predeformation on microstructure and mechanical properties of Al–Cu–Li–Zr alloy containing Sc

Abstract: The effects of prior cold deformation on the microstructures and the room temperature mechanical properties of an Al-3 . 5Cu-1 . 5Li-0 . 22(SczZr) alloy have been observed by using TEM and tensile test at room temperature. The results show that the alloy has the character of aging hardening, and the major phase of precipitation and strengthening is T 1 phase. The result also show that prior cold deformation leads to more dispersive and uniform distribution of T 1 precipitations. It accelerates aging response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Flow transition in melt under the interaction of buoyancy, thermocapillary force and crystal and/or crucible rotation in the Cz configuration have been widely studied by experiments and numerical simulations. The results indicated that the transition from axisymmetric flow to nonaxisymmetric flow is due to the interaction between the horizontal temperature gradient and the Coriolis force ͑known as baroclinic instability͒, 6,11,[32][33][34] or interactions between the vertical temperature gradient and the Coriolis force ͑known as Küpper-Lortz instability͒, 7 or the Marangoni effect ͑known as Marangoni instability͒. [20][21][22] In this study, there is no temperature difference, thus the baroclinic, Küpper-Lortz, and Marangoni instabilities are all unsuitable.…”
Section: -5mentioning
confidence: 90%
“…Flow transition in melt under the interaction of buoyancy, thermocapillary force and crystal and/or crucible rotation in the Cz configuration have been widely studied by experiments and numerical simulations. The results indicated that the transition from axisymmetric flow to nonaxisymmetric flow is due to the interaction between the horizontal temperature gradient and the Coriolis force ͑known as baroclinic instability͒, 6,11,[32][33][34] or interactions between the vertical temperature gradient and the Coriolis force ͑known as Küpper-Lortz instability͒, 7 or the Marangoni effect ͑known as Marangoni instability͒. [20][21][22] In this study, there is no temperature difference, thus the baroclinic, Küpper-Lortz, and Marangoni instabilities are all unsuitable.…”
Section: -5mentioning
confidence: 90%
“…This was attributed to the heterogeneous precipitation of ␤ 1 (FCC) phase by the authors [10]. Such a thermomechanical processing with predeformation between solution treatment and artificial aging is extensively used in aluminum alloys [11][12][13][14], but rarely in magnesium alloys. Therefore, it should be meaningful to introduce pre-deformation practice into magnesium alloys, especially the newly developed high strength Mg-RE alloys, and perform further study on the structure-property relationships.…”
Section: Introductionmentioning
confidence: 99%
“…During artificial ageing, these Al–Li–Cu alloys are strengthened by a number of precipitates such as δ′, θ′, T 1 and S′. The artificial ageing response of Al–Li–Cu alloys has been found to be accelerated by plastic deformation prior to ageing owing to the introduction of dislocations (Kumar et al , 1990; Ringer et al ,1995; Liang et al , 2007). Ringer et al .…”
Section: Introductionmentioning
confidence: 99%